GLOBECOM 2009 - 2009 IEEE Global Telecommunications Conference 2009
DOI: 10.1109/glocom.2009.5425315
|View full text |Cite
|
Sign up to set email alerts
|

Joint Scheduling and Instantaneously Decodable Network Coding

Abstract: Abstract-We consider a wireless multi-hop network and design an algorithm for jointly optimal scheduling of packet transmissions and network coding. We consider network coding across different users, however with the restriction that packets have to be decoded after one hop. We compute the stability region of this scheme and propose an online algorithm that stabilizes every arrival rate vector within the stability region. The online algorithm requires computation of stable sets in an appropriately defined conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 15 publications
(22 reference statements)
0
44
0
Order By: Relevance
“…It has shown that it can significantly improve transmission efficiency, throughput and delay over wireless erasure channels [22,[31][32][33][34][35][36][37][38][39][40][41][42]. It can provide several more spectrum holes for the CRN to use by speeding up the packet transmission and recovery in the PN.…”
Section: Previous Workmentioning
confidence: 99%
“…It has shown that it can significantly improve transmission efficiency, throughput and delay over wireless erasure channels [22,[31][32][33][34][35][36][37][38][39][40][41][42]. It can provide several more spectrum holes for the CRN to use by speeding up the packet transmission and recovery in the PN.…”
Section: Previous Workmentioning
confidence: 99%
“…Network stability has also been studied along with network coding schemes in [5] and [6], albeit in different contexts. In [5], the stability of single hop BEC with feedback is examined but the traffic considered is broadcast and linear network coding schemes are used, so there is no guarantee for instantaneous decodability.…”
Section: Introductionmentioning
confidence: 99%
“…A linear optimization framework for packing butterflies is proposed in [6]. Scheduling over coded wireless networks is considered, and the computational complexity of scheduling and network coding is discussed in [20], [21], [22] This paper combines the NCAQM and NCAPP mechanisms proposed independently in [2] and [3], respectively. We first show that these mechanisms are complementary: NCAQM creates coding opportunities (which is necessary in high load regimes) while NCAPP drains coded faster than uncoded packets (which is important in low load regimes).…”
Section: Related Workmentioning
confidence: 99%